2008
DOI: 10.1287/mnsc.1080.0879
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing in the Field: A Heuristic Processing Model

Abstract: This research uses dual-process cognitive theory to describe how people process information differently when it is delivered via videoconference rather than when it is delivered face-to-face. According to this theory, relative to face-to-face communication, people in videoconferences tend to be more influenced by heuristic cues--such as how likeable they perceive the speaker to be--than by the quality of the arguments presented by the speaker. This is due to the higher cognitive demands that videoconferencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 54 publications
4
78
0
1
Order By: Relevance
“…PIP is expected to increase self-focused attention, which has been shown to increase cognitive load (Panayiotou & Vrana, 1998;Silvia, 2002;Vallacher, 1978). In general, video communication has been shown to induce higher cognitive load compared with face-to-face (Ferran & Watts, 2008) and audio (Hinds, 1999). Because PIP technology presents more pieces of information to integrate, through increased self-focused attention and attentional distractions, we predict that interviewees will experience increased cognitive load.…”
Section: Social Facilitationmentioning
confidence: 99%
“…PIP is expected to increase self-focused attention, which has been shown to increase cognitive load (Panayiotou & Vrana, 1998;Silvia, 2002;Vallacher, 1978). In general, video communication has been shown to induce higher cognitive load compared with face-to-face (Ferran & Watts, 2008) and audio (Hinds, 1999). Because PIP technology presents more pieces of information to integrate, through increased self-focused attention and attentional distractions, we predict that interviewees will experience increased cognitive load.…”
Section: Social Facilitationmentioning
confidence: 99%
“…This illusion of co-presence and the comparison with face to face interaction, especially with video-conferencing communication, has been an issue in the literature. Previous research with medical professionals (Ferran and Watts, 2008) found that participants in video-conferencing sessions were more influenced by the likeability of the presenter than the arguments being presented.…”
Section: Observations From the Use Of Access Grid Technologymentioning
confidence: 98%
“…Therefore, it is environmentally friendly, convenient and good for building relationships (Earon, 2014: 2;Harrin, 2010a). Some disadvantages are signal latency and that it can cause anxiety (Wolfe, 2007: 119-126); delegates must work harder to interpret the information presented in the conference (Ferran & Watts, 2008), and lack of eye contact and appearance consciousness (Benson-Armer & Hsieh, 1997 (Harrin, 2010b).…”
Section: Computer-mediated Communicationmentioning
confidence: 99%